2004
DOI: 10.1089/089771504772695896
|View full text |Cite
|
Sign up to set email alerts
|

Marked Gender Effect on Lipid Peroxidation after Severe Traumatic Brain Injury in Adult Patients

Abstract: Striking gender differences have been reported in the pathophysiology and outcome of acute neurological injury. Greater neuroprotection in females versus males may be due, in part, to direct and indirect sex hormone-mediated antioxidant mechanisms. Progesterone administration decreases brain levels of F(2)-isoprostane, a marker of lipid peroxidation, after experimental traumatic brain injury (TBI) in male rats, and estrogen is neuroprotective in experimental neurological injury. In this study, we evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(103 citation statements)
references
References 34 publications
5
96
1
1
Order By: Relevance
“…12,13,23 Cerebrospinal fluid F2-isoprostanes are a unique series of prostaglandin-like compounds formed in vivo from the free radical-catalyzed peroxidation of arachidonic acid and have been used to assess peroxidation in patients with severe TBI. 3,4,17,35 Glycerol is an end product of phospholipid degradation in neural tissue cell membranes and is a marker of cell damage whether caused by O 2 toxicity via free radical formation and lipid peroxidation or secondarily from ischemia. 16,19,32 Levels of CSF F2-isoprostanes as well as microdialysate glycerol were significantly decreased following combined HBO 2 /NBH treatment.…”
Section: Oxygen Toxicitymentioning
confidence: 99%
“…12,13,23 Cerebrospinal fluid F2-isoprostanes are a unique series of prostaglandin-like compounds formed in vivo from the free radical-catalyzed peroxidation of arachidonic acid and have been used to assess peroxidation in patients with severe TBI. 3,4,17,35 Glycerol is an end product of phospholipid degradation in neural tissue cell membranes and is a marker of cell damage whether caused by O 2 toxicity via free radical formation and lipid peroxidation or secondarily from ischemia. 16,19,32 Levels of CSF F2-isoprostanes as well as microdialysate glycerol were significantly decreased following combined HBO 2 /NBH treatment.…”
Section: Oxygen Toxicitymentioning
confidence: 99%
“…In adults, a gender bias was found in that males had approximately twice the levels of CSF F2-isoprostane than females, and only males had decreased levels of this lipid metabolite in response to hypothermia. 86 This disparity in lipid peroxidation has been proposed to be a potential reason for the greater neuroprotection seen in females than in males. Although F2-isoprostane levels have been called the "gold standard" of lipid peroxidation, determination of its levels requires specialized equipment, thereby limiting its clinical usefulness.…”
Section: F2-isoprostanementioning
confidence: 99%
“…me 13,17) . Other authors have reported that sexual dysmorphism may play an important role in outcome following TBI 1,22) . The mechanism by which gender may influence the outcome following TBI is not yet clear.…”
Section: Discussionmentioning
confidence: 97%